Examining the Relationship Between Community Integration and Mental Health Characteristics of Individuals With Childhood Acquired Neurological Disability - Nguyen, Christine; Leung, Abigail; Lauzon, Andrea; Bayley, Mark T.; Langer, Laura L.; Luong, Dorothy; Munce, Sarah E. P. (Frontiers in Pediatrics, 2021)
Background: Many individuals with Cerebral Palsy (CP) or Acquired Brain Injury (ABI) are at higher risk of lowered psychosocial functioning, poor mental health outcomes and decreased opportunities for community integration (CI) as they transition to adulthood. It is imperative to understand the characteristics of those at highest risk of dysfunction so that targeted interventions can be developed to reduce the impact. Methods: This quantitative, cross-sectional study examines current patients of the Living Independently Fully Engaged (LIFEspan Service), a tertiary outpatient hospital-based clinic. The Patient Health Questionnaire-4 (PHQ-4) and the Community Integration Questionnaire (CIQ) were administered to participants. Personal health information was also collected from participants’ health charts, and participant interviews. Associations of sex and condition with the outcomes of screening for further assessment of depression, screening for further assessment of anxiety, and CI were calculated using t-tests and Chi-square tests. Results: 285 participants completed standardized screening tools for depression and anxiety (PHQ-4) and 283 completed the Community Integration Questionnaire (CIQ). Mean age was 23.4 (4.2) years, 59% were diagnosed with CP, 41% diagnosed with ABI, and 56% were male. A moderate proportion of the population screened positive for further assessment of anxiety (28%) and depression (16%), and the overall mean score on the CIQ for the population was 15.8 (SD 5.1). Participants that screened positive for further assessment of depression and anxiety on the PHQ4 had lower scores on the Social Integration subscale of the CIQ (p=0.04 and p=0.036, respectively). Females were found to have significantly higher community integration than males (p=0.0011) and those diagnosed with ABI were found to have significantly higher community integration than those with CP (p=0.009), respectively. A weak negative association was found between age for the total sample and overall PHQ4 score (p=0.0417). Presence of an intellectual or learning disability/challenge was associated with a lower CIQ score (p=0.0026). Conclusions: This current study, highlights the need for further research to explore the unique needs and barriers faced by this population. This study may inform assessments and interventions to support the mental health and community integration of this population.